2023
DOI: 10.20944/preprints202307.1256.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Correlation between Neck Pain and Disability, Forward Head Posture and Hyperkyphosis with Opium Smoking in the Most Prevalent Opium Smoking Persian Gulf Country; a Cross-sectional Study from Iran

Abstract: Opium smoking for long hours and over many years is common in Iran, and the Covid-19 pan-demic and false beliefs about the protective effects of that opium against COVID-19 infection has caused the increasing of opium smoking during the pandemic. The aim of this study was to in-vestigate the relationship between non-ergonomic positions of traditional opium smoking in Iran with the occurrence of neck pain and disability, forward head posture and hyperkyphosis. In this cross-sectional and correlation study 120 p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
(1 reference statement)
0
1
0
Order By: Relevance
“…Studies conducted on dentists and farmers have also confirmed the effect of harmful positions due to work-related posture with a higher probability of neck pain and disability (34,35). Considering that in the previous studies, there has been no correlation between neck pain and disability and FHP with the drug use duration (36), it seems that the causal relationship with opium smoking duration is strengthened.…”
Section: Discussionmentioning
confidence: 85%
“…Studies conducted on dentists and farmers have also confirmed the effect of harmful positions due to work-related posture with a higher probability of neck pain and disability (34,35). Considering that in the previous studies, there has been no correlation between neck pain and disability and FHP with the drug use duration (36), it seems that the causal relationship with opium smoking duration is strengthened.…”
Section: Discussionmentioning
confidence: 85%